Efficacy of first-line tocilizumab therapy in early polymyalgia rheumatica: a prospective longitudinal study. Issue 8 (29th February 2016) - Devauchelle-Pensec, Valérie; Berthelot, Jean Marie; Cornec, Divi; Renaudineau, Yves; Marhadour, Thierry; Jousse-Joulin, Sandrine; Querellou, Solène; Garrigues, Florent; De Bandt, Michel; Gouillou, Maelenn; Saraux, Alain
Abstract : Background: Glucocorticoids are the cornerstone treatment of polymyalgia rheumatica (PMR) but induce adverse events. Objectives: To evaluate the efficacy and safety of first-line tocilizumab in PMR. Methods: In a prospective open-label study (ClinicalTrials.gov: NCT01713842 ), 20 glucocorticoid-free patients fulfilling Chuang's PMR criteria, with symptom onset within the last 12 months and a PMR activity score (PMR-AS) >10, each received three tocilizumab infusions at 4-week intervals, without glucocorticoids, followed by oral prednisone from weeks 12 to 24 (0.15 mg/kg if PMR-AS ≤10 and 0.30 mg/kg otherwise). The primary end point was the proportion of patients with PMR-AS≤10 at week 12. Results: Baseline median PMR-AS was 36.6 (IQR 30.4–43.8). At week 12, all patients had PMR-AS≤10 and received the low prednisone dosage. Median PMR-AS at weeks 12 and 24 was 4.5 (3.2–6.8) and 0.95 (IQR 0.4–2), respectively (p<0.001 vs baseline for both time points). No patient required rescue treatment. Positron emission tomography-CT showed significant improvements. The most common adverse events were transient neutropenia (n=3) and leucopenia (n=5); in one patient, the second tocilizumab infusion was omitted due to leucopenia. Conclusions: Tocilizumab monotherapy is effective in recent-onset PMR. Randomised controlled trials are warranted. Trial registration number: NCT01713842.